ASSOCIATION BETWEEN INHALED CORTICOSTEROIDS AND OSTEOPOROSIS: A REVIEW - Ulfa Mustofa Nurfadilasari; Sternatami Liberitera (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Inhaled corticosteroids (ICS) are commonly prescribed to manage asthma and chronic obstructive pulmonary disease (COPD) due to their local anti-inflammatory effects in the airways. However, prolonged or high-dose ICS use has been associated with systemic adverse effects, including decreased bone mineral density (BMD) and increased risk of osteoporosis. This review aimed to examine the association between ICS use and the risk of osteoporosis or fractures, and to identify modifying factors such as dose, duration, patient age, sex, and type of corticosteroid used. Literature review was conducted using databases including PubMed, Scopus, and Web of Science. Articles were selected using specific inclusion and exclusion criteria. The review focused on original studies published up to March 2025, resulting in 28 relevant articles, of which 6–8 high-quality studies were analyzed in depth. Most studies demonstrated that long-term or high-dose ICS use is associated with decreased BMD and increased risk of fractures, especially in elderly COPD patients. The greatest risk was linked to fluticasone and budesonide at doses ≥500 µg/day. Some studies found neutral or even protective effects in specific subgroups, indicating population-dependent variability. Meta-analyses revealed conflicting results due to heterogeneity in populations and methodologies. High-dose and long-term ICS use may increase the risk of osteoporosis. Clinicians should consider individualized risk assessments and adopt strategies such as using the lowest effective dose, monitoring BMD, and providing calcium and vitamin D supplementation in at-risk populations.